Finding of the steppe whiskered bat (Myotis aurascens Kuzyakin, 1935) in the Southeast of Ukraine - A. Bronskov (Праці Теріологічної школи, 2017)
The record of the steppe whiskered bat near Huselschikove village, Novoazovsky district, Donetsk region (Ukraine) has been described. Earlier this species was recorded using ultrasonic heterodyne detector in the area west of the village Bezimenne in late July 2008. Now bats are found on the right bank of the Hruzky Yelanchyk river, in a natural cave of karst origin. We found 2 individuals on 15 March, 2013, and 4 individuals on both 22 and 30 March, 2013. In the previous period (from the 21st of February, 2013) the average daily temperature does not drop below 00C. We suppose the wintering of the bats in this cave.